2018
DOI: 10.1080/10428194.2018.1543880
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid and 6-formylindolo(3,2-b)carbazole (FICZ) combination therapy reveals putative targets for enhancing response in non-APL AML

Abstract: In non-APL AML, identification of a signaling signature would predict potentially actionable targets to enhance differentiation effects of all-trans-retinoic acid (RA) and make combination differentiation therapy realizable. Components of such a signaling machine/signalsome found to drive RA-induced differentiation discerned in a FAB M2 cell line/model (HL-60) were further characterized and then compared against AML patient expression profiles. FICZ, known to enhance RA-induced differentiation, was used to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…For example, our laboratory reported that the SFK inhibitors PP2, dasatinib, and bosutinib modulate MAPK signaling and enhance the therapeutic effects of ATRA in various myeloid leukemia cells [9,40]. We have also found that AhR ligands, specifically FICZ and VAF347, used with ATRA enhance induced differentiation [57,58]. www.oncotarget.com…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, our laboratory reported that the SFK inhibitors PP2, dasatinib, and bosutinib modulate MAPK signaling and enhance the therapeutic effects of ATRA in various myeloid leukemia cells [9,40]. We have also found that AhR ligands, specifically FICZ and VAF347, used with ATRA enhance induced differentiation [57,58]. www.oncotarget.com…”
Section: Discussionmentioning
confidence: 97%
“…Such therapies hold the promise of both overcoming resistance and mitigating the incidence of retinoic acid syndrome, a potentially fatal cardio-pulmonary pathological sequela of ATRA therapy, by reducing the effective dose of ATRA needed. Much effort has been devoted to identifying novel drugs with specific targets that would increase the therapeutic efficiency of ATRA [54][55][56][57][58]. In a series of studies, we have established that ATRA-induced differentiation and cell cycle arrest of a FAB M2 cell line model requires formation and activation of a macromolecular signaling complex, a signalsome, that incorporates a number of signaling molecules associated with MAPK pathway signal transduction as well as unexpected components, in particular the IRF-1 and AhR transcription factors [10,57].…”
Section: Discussionmentioning
confidence: 99%
“…AHR is also operating by non-genomic signaling including protein kinases (Puga et al 2009). For example, it operates as component of E3 ubiquitin ligases (Ohtake et al 2009) and of a signalsome (Bunaciu et al 2019). Furthermore, AHR often operates in cross-talk with other transcription factors including Nrf2, the key protector against oxidative stress (Kensler et al2007) and NF-κB (Vogel et al 2014).…”
Section: Ahr Ligands and Signalingmentioning
confidence: 99%
“…This process has been shown to depend on calcium mobilization mediated by cyclic ADP-ribose (Partida-Sanchez et al 2001). Interestingly, CD38 together with AHR is a constituent of a signalsome (Bunaciu et al 2019), probably regulating microbial defense.…”
Section: Nad + Consuming Enzymes (Cd38 Parps and Nad + -Dependent Sirtuins)mentioning
confidence: 99%
“…HL-60 is a myelo-monocytic (granulocyte-monocyte) precursor cell that bears fidelity to a RA-responsive t (15,17)-negative subtype of AML. 16,40 Interferon is a regulator of myelo-monopoiesis. The primary mediator of the cellular effects of interferon is the IRF-1 transcription factor.…”
Section: Irf-1 Disruption Suppressed D3induced Ros Without Affecting Differentiationmentioning
confidence: 99%